The role of the tapetum in the formation of sporopollenin-containing structures during microsporogenesis in Pinus banksiana. - Dickinson, H; Bell, P (1972)
In the microsporangium of Pinus the outer layer of the peritapetal membrane and the pro-orbicular cores are not only formed in a similar manner, but are composed of apparently identical materials. Precursors for this lipoidal material are produced by the tapetal protoplasts, as are the precursors of sporopollenin. Production the precursors is sequential and appears to involve different cytoplasmic structures.The sporopollenin synthesised by the tapetum condenses upon the pro-orbicular cores, the peritapetal membrane, the exine initials and, on fragmentation of the tapetum, parts of the disintegrating cytoplasm. The evident unpolarised nature of the tapetal protoplasts, and the sequential nature of the synthesis of the lipoid and the sporopollenin by them, may point to orbicule formation in gymnosperms being a necessary by-product of the development of the peritapetal membrane.